The Innkeeper of Ivy Hill - Klassen, Julie 1964-; Baker Publishing Group (Minneapolis, Minnesota : Bethany House, a division of Baker Publishing Group, 2016)
When her husband dies suddenly, Jane Bell becomes the reluctant landlady of The Bell, an inn in the village of Ivy Hill. Jane has no idea how to manage a business, but with the town's livelihood at stake and a large loan due, she must quickly find a way to save the inn. Despite their strained relationship, Jane turns to her mother-in-law, Thora, for help.
Keywords: Hotelkeepers -- Fiction; Widows -- Fiction; Mothers-in-law -- Fiction; Man-woman relationships -- Fiction; England -- Fiction -- Social life and customs -- 19th century; Romance fiction; Historical fiction; Religious fiction